2022
DOI: 10.1124/molpharm.121.000374
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms to Repair Stalled Topoisomerase II-DNA Covalent Complexes

Abstract: DNA topoisomerases regulate the topological state of DNA, relaxing DNA supercoils and resolving catenanes and knots that result from biological processes such as transcription and replication. DNA topoisomerase II (TOP2) enzymes achieve this by binding DNA and introducing an enzyme-bridged DNA double-strand break (DSB) where each protomer of the dimeric enzyme is covalently attached to the 5' end of the cleaved DNA via an active site tyrosine phosphodiester linkage. The enzyme then passes a second DNA duplex t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Canonically, the transient enzyme-linked strand breaks formed during the reaction cycle remain buried within the enzyme as TOP2-covalent DNA complexes (TOP2-CCs) and are rapidly resolved after strand-passage (Figure 1A,B). However, if religation is impeded, TOP2-CCs can be processed to protein free DSBs (pf-DSBs) [5] which can initiate a DNA damage response including phosphorylation of histone H2AX (Figure 1C). This leads to the question of whether these promoter-associated, signalinduced, TOP2B-dependent DSBs are the incidental consequence of occasional failure of TOP2 to quickly complete its reaction cycle or are part of a mechanism that specifically requires the formation of distinct pf-DNA DSBs for efficient transcriptional induction (see Section 6).…”
Section: Top2b and Stimulus-induced Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canonically, the transient enzyme-linked strand breaks formed during the reaction cycle remain buried within the enzyme as TOP2-covalent DNA complexes (TOP2-CCs) and are rapidly resolved after strand-passage (Figure 1A,B). However, if religation is impeded, TOP2-CCs can be processed to protein free DSBs (pf-DSBs) [5] which can initiate a DNA damage response including phosphorylation of histone H2AX (Figure 1C). This leads to the question of whether these promoter-associated, signalinduced, TOP2B-dependent DSBs are the incidental consequence of occasional failure of TOP2 to quickly complete its reaction cycle or are part of a mechanism that specifically requires the formation of distinct pf-DNA DSBs for efficient transcriptional induction (see Section 6).…”
Section: Top2b and Stimulus-induced Gene Expressionmentioning
confidence: 99%
“…In this article, we will elaborate on the specific roles of TOP2B in transcription focusing on the nature of the DSBs observed at activated promoters and on the reported protein interactions of TOP2B with established protein complexes and individual proteins associated with transcription-related processes. Figure 1C) [5]. Topoisomerases are involved in many types of DNA transaction, from replication and recombination to DNA repair and gene expression [6].…”
Section: Introductionmentioning
confidence: 99%
“…Anthracyclines bind to DNA and topoisomerase II (topo II), which hinders the re-ligation of the DNA double strands, and persistent DNA double-strand break (DSB) was generated consequently. DSB is lethal to cells and brings about p53 activation and cell death [ 13 ]. Zhang et al [ 14 ] found that the deletion of topo IIβ from cardiomyocytes prevented mice from developing AIC, suggesting the critical role of topoisomerase-mediated DSB in the pathomechanism of AIC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cells have a diverse repertoire of DNA repair and damage tolerance mechanisms to prevent topoisomerase-induced genome instability (Weickert and Stingele, 2022). These various pathways include DNA damage signaling, removal of proteins bound to DNA by proteolysis (Li and Liu, 2001), and a variety of nucleolytic enzymes that can excise phosphotyrosyl-linked peptides (Yang et al, 1996;Cortes Ledesma et al, 2009) or carry out endonucleolytic cleavage to remove DNA/protein crosslinks (Swan et al, 2022) MRE11 is a double strand break (DSB) repair enzyme with endonuclease and 3′ to 5′ exonuclease activities, acting in a functional protein complex with RAD50 and NBS1. The MRE11-RAD50-NBS1 (MRN) complex plays a central role in sensing and initial processing of DSB termini to promote HR or NHEJmediated repair (Paull, 2018).…”
Section: Introductionmentioning
confidence: 99%